EFFECT OF CONSUMING PAPAYA (CARICA PAPAYA LINN.) ON THE LEVEL OF HEMOGLOBIN AND HEMATOCRIT IN PREGNANT WOMEN WITH ANEMIA - Choralina Eliagita; Tjahjono Kuntjoro; Sri Sumarni; Ari Suwondo; Soeharyo Hadisaputro; Choralisa Eliagita; Donny Kristanto Mulyantoro (Belitung Nursing Journal, 2017)
Background: The prevalence of anemia among pregnant women is still high in Indonesia, especially in Bengkulu. Consuming papaya is considered as one of the solutions to increase hemoglobin and hematocrit level. Objective: This study aims to examine the effect of consuming papaya on the level of hemoglobin and hematocrit in pregnant women. Methods: This study employed a true experiment with randomized pretest and posttest design with control group. There were 42 respondents recruited in this study using simple random sampling. Randomization was performed to divide the samples into two groups, namely 21 respondents in a treatment group and 21 respondents in a control group. A total of 110 grams of papaya was given to the intervention group every day for 14 days. Data were analyzed using dependent t-test and independent t-test. Result: There was a significant effect of consuming papaya on the hemoglobin and hematocrit level with p-value 0.000 (< .05). The mean difference between two groups showed that hemoglobin level (control group 10.010 gr/dL; intervention group 10.838 gr/dL) and hematocrit level (control group 27.43 %; intervention group 30.10 %). Conclusion: Consuming papaya has a significant effect on changes in hemoglobin and hematocrit levels. It is suggested that consuming papaya should be one of alternative treatments for midwives to prevent anemia in pregnant women.